Clear Cell Odontogenic Carcinoma of the Mandible Harboring EWSR1 Rearrangement: Report of a Massive Jaw Tumor and Review of Diagnostic Considerations - Adepitan A. Owosho; Chukwubuzor Okwuosa; Donald I. Obi; Robinson O. Okiti; Kurt F. Summersgill (Case Reports in Dentistry)
Clear cell odontogenic carcinoma (CCOC) is a low-grade malignant neoplasm that affects the jaws. We report an 18 cm massive case of mandibular CCOC in a 43-year-old female. The tumor was composed of nests and cords of round to polygonal monomorphic clear cells separated by prominent stromal hyalinization. Immunohistochemically, the tumor cells showed focal cytokeratin 5/6 positivity and intracytoplasmic PAS-positive granules and were negative for S100 and after diastase treatment (PAS-D). Molecularly, this case was positive for EWSR1 rearrangement by FISH. The following should be included in the histopathological differential diagnosis: hyalinizing clear cell carcinoma of the salivary gland, clear cell variant of central mucoepidermoid carcinoma, clear cell variant of calcifying epithelial odontogenic tumor, and metastatic renal cell carcinoma. CCOC is a rare entity, with only 79 cases reported in the mandible. This case highlights the propensity for CCOC to exhibit invasiveness, destructive nature, and facial disfigurement if left untreated.